Compassionate use of meropenem/vaborbactam for infections caused by KPC-producing Klebsiella pneumoniae: a multicentre study. Issue 1 (7th March 2022) - Tumbarello, Mario; Raffaelli, Francesca; Cascio, Antonio; Falcone, Marco; Signorini, Liana; Mussini, Cristina; De Rosa, Francesco Giuseppe; Losito, Angela Raffaella; De Pascale, Gennaro; Pascale, Renato; Giacobbe, Daniele Roberto; Oliva, Alessandra; et al.
Abstract: Objectives: To explore the real-life performance of meropenem/vaborbactam for treating serious KPC-producing Klebsiella pneumoniae infections, including those resistant to ceftazidime/avibactam. Methods: A retrospective observational cohort study was conducted in 12 Italian hospitals. Enrolled patients had K. pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC- Kp ) infections (59.5% of which were ceftazidime/avibactam resistant). Patients who received ≥72 h of meropenem/vaborbactam therapy (with or without other antimicrobials) in a compassionate-use setting were included. Results: The 37 infections (all hospital-acquired) were mainly bacteraemic (BSIs, n = 23) or lower respiratory tract infections (LRTIs, n = 10). Clinical cure was achieved in 28 (75.6%) cases and microbiologically confirmed in all 25 with follow-up cultures. Three (10.7%) of the 28 clinical cures (all BSIs, 2/3 microbiologically confirmed) were followed by in-hospital recurrences after meropenem/vaborbactam was discontinued (median interval: 18 days). All three recurrences were susceptible to meropenem/vaborbactam and successfully managed with meropenem/vaborbactam combined with colistin or fosfomycin. Nine patients (24.3%) (all with BSIs or LRTIs) died in hospital with persistent signs of infection. Most were aged over 60 years, with high comorbidity burdens and INCREMENT scores ≥8. Only one had received meropenem/vaborbactam monotherapy. Six began meropenem/vaborbactam therapy >48 h after infection onset. Outcomes were unrelated to the isolate's ceftazidime/avibactam susceptibility status. The single adverse event observed consisted of severe leukopenia with thrombocytopenia. Conclusions: With the well-known limitations of real-life retrospective studies, our results support previous findings indicating that meropenem/vaborbactam therapy will be a safe, effective tool for managing serious KPC- Kp infections, including the increasing proportion displaying resistance to ceftazidime/avibactam.